2004
DOI: 10.1002/eji.200425210
|View full text |Cite
|
Sign up to set email alerts
|

Activating CD94:NKG2C and inhibitory CD94:NKG2A receptors are expressed by distinct subsets of committed CD8+ TCR αβ lymphocytes

Abstract: A subset of CD8 + T cells express the natural killer cell receptors CD94:NKG2A or CD94:NKG2C. We found that although many CD8 + T cells transcribe CD94 and NKG2C, expression of a functional CD94:NKG2C receptor is restricted to highly differentiated effector cells. CD94:NKG2A is expressed by a different subset consisting of CCR7 + memory cells and CCR7 -effector cells. Since NKG2A can only be induced on naive CD8 + T cells while CD94 -memory cells are refractory, it is likely that commitment to the CD94:NKG2A +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 36 publications
4
51
0
Order By: Relevance
“…CD94 can only exert its signaling function when heterodimerized with either NKG2A (inhibiting dimer) or NKG2C (activating dimer). The intensity of CD94 expression is, as reported by Arlettaz et al (27), high in conjunction with NKG2A but low when bound to NKG2C. During the first weeks of the CMV response, predominantly CD94 dim cells appeared in the circulation (Fig.…”
Section: Cd94 Dimerizes With Different Kinetics With Nkg2c and Nkg2asupporting
confidence: 73%
See 2 more Smart Citations
“…CD94 can only exert its signaling function when heterodimerized with either NKG2A (inhibiting dimer) or NKG2C (activating dimer). The intensity of CD94 expression is, as reported by Arlettaz et al (27), high in conjunction with NKG2A but low when bound to NKG2C. During the first weeks of the CMV response, predominantly CD94 dim cells appeared in the circulation (Fig.…”
Section: Cd94 Dimerizes With Different Kinetics With Nkg2c and Nkg2asupporting
confidence: 73%
“…The NKG2A/B/CD94 is an inhibitory receptor, whereas the NKG2C/CD94 and NKG2E/H/CD94 are activating receptors (32). Arlettaz et al (27) reported that CD94 bright expression is associated with NKG2A and CD94 dim is associated with NKG2C, although also other NKG2 proteins may dimerize with CD94. Our observation that CD94 dim was primarily enhanced during the acute phase of the infection, whereas CD94 bright accounted for the latent phase was confirmed by the quick rise in NKG2C followed by robust expansion of NKG2A which continued to expand for at least 40 wk after the peak of the viral load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these receptors are also expressed on a subset of cytotoxic T lymphocytes (Arlettaz et al, 2004). Little is known about interactions of HLA-E with T lymphocytes in glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…NKG2A, B, C, E, or F receptors are expressed on NK cells, CD8 + TCR  and  lymphocytes, CD4 + T cell subsets, and NKT cells (1,10,(22)(23)(24)(25), all of which recognize HLA-E (17,21,(26)(27)(28) complexed to an MHC class I leader sequence (29). In this fashion, they monitor the expression of MHC-I molecules on target cells.…”
Section: Introductionmentioning
confidence: 99%